1993
DOI: 10.1093/oxfordjournals.aje.a116721
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Childhood Cancer for Infants with Birth Defects

Abstract: To attempt to confirm associations found in a companion study in Atlanta, Georgia between Down's syndrome and acute leukemia and between pyloric stenosis and childhood cancer, the authors used the State Health Registry of Iowa to link the records of infants and children with cancer for 1983 to 1989 with the records of infants with birth defects for 1983 to 1988. During the study period, birth defects were diagnosed in 10,891 infants younger than 1 year of age, and cancer was diagnosed in 396 children younger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
1
19
2
Order By: Relevance
“…This is at variance with some prior findings [8][10], [14], [15], [48]. The incorporation of clinical record review in our study could explain some of the discrepancies.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This is at variance with some prior findings [8][10], [14], [15], [48]. The incorporation of clinical record review in our study could explain some of the discrepancies.…”
Section: Discussioncontrasting
confidence: 97%
“…For Down syndrome, prior studies [7][10], [12], [13], [17], [51][53] reported similar risk patterns, with some variation in the magnitude of the estimates. Children with trisomy 13 or 18 had a different risk profile.…”
Section: Discussionmentioning
confidence: 71%
“…While earlier studies suggest individuals born with clefts and their family members report more often cancer [2][3][4][5][6][7], the results of the present study contradict those findings. This study agrees with at least one previous investigation [38] that also did not find an association between oral clefts and cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…Individuals born with oral clefts have a shorter lifespan and may have a higher incidence of cancer [2][3][4][5][6][7]. Families of individuals born with oral clefts report more often cancer [8][9][10][11] and, conversely, isolated oral clefts were reported more often in families in which one individual was diagnosed with cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Danish cleft lip and palate register is described elsewhere 79. We excluded infants with malformations other than cleft lip and palate to eliminate the effect of multiple anomalies on increased mortality.…”
Section: Methodsmentioning
confidence: 99%